The viral hypothesis in Alzheimer’s disease: SARS-CoV-2 on the cusp - Liu, Nanyang; Jiang, Xuefan; Li, Hao (Frontiers in Aging Neuroscience, 2023)
Increasing evidence highlights that infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has long-term effects on cognitive function, which may cause neurodegenerative diseases like Alzheimer's disease (AD) in the future. We performed an analysis of a possible link between SARS-CoV-2 infection and AD risk and proposed several hypotheses for its possible mechanism, including systemic inflammation, neuroinflammation, vascular endothelial injury, direct viral infection, and abnormal amyloid precursor protein metabolism. The purpose of this review is to highlight the impact of infection with SASR-CoV-2 on the future risk of AD, to provide recommendations on medical strategies during the pandemic, and to propose strategies to address the risk of AD induced by SASR-CoV-2. We call for the establishment of a follow-up system for survivors to help researchers better understand the occurrence, natural history, and optimal management of SARS-CoV-2-related AD and prepare for the future.